2014
DOI: 10.9790/5736-07725057
|View full text |Cite
|
Sign up to set email alerts
|

Nitration of Benzene Using Mixed Oxide Catalysts

Abstract: Vapor phase nitration of benzene has been carried out, using dilute nitric acid as the nitrating agent, over Fe/Mo/SiO 2 solid acid catalyst with more than 80% benzene conversion and 99% selectivity for mononitrobenzene. A series of Fe/Mo/SiO 2 catalysts with various compositions were prepared using a sol-gel technique and characterized using X-ray diffraction analysis (XRD), BET specific surface area analysis, temperature-programmed desorption (TPD) of ammonia, and FTIR spectroscopic analysis of adsorbed pyri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Some works [21,46] were based on gas phase nitration using diluted nitric acid (30 wt%). One important advantage of using diluted nitric acid was the possibility of increasing the maximum reaction temperature for nitration up to 200 °C, whereas the diluted acid shows less oxidative behavior and higher resistance to the decomposition processes (reduction of SNO).…”
Section: Effect Of Temperature and Concentration Of Nitric Acidmentioning
confidence: 99%
“…Some works [21,46] were based on gas phase nitration using diluted nitric acid (30 wt%). One important advantage of using diluted nitric acid was the possibility of increasing the maximum reaction temperature for nitration up to 200 °C, whereas the diluted acid shows less oxidative behavior and higher resistance to the decomposition processes (reduction of SNO).…”
Section: Effect Of Temperature and Concentration Of Nitric Acidmentioning
confidence: 99%
“…Certain zeolites, modified metal oxides, and silica-supported heteropolyacids have been studied to achieve efficient liquid–solid nitration reactions without using sulfuric acid. It is not surprising that nitration using potent solid catalysis coupled with continuous-flow chemistry can be an ideal way to address the issues associated with this process; indeed, several examples have been developed for vapor-phase flow nitration reactions using solid acid catalysts. A representative work by Koskin et al described a comparison of solid acid candidates under vapor-phase flow conditions with concentrated and diluted nitric acid as nitration agents and revealed that MoO 3 /SiO 2 had the best catalytic activity, giving the product in 95% yield at 1.42 h –1 weight hourly space velocity (WHSV) . Nevertheless, trials for liquid-phase reactions that expand the scope of applicable substrates for aromatics are lacking.…”
Section: Introductionmentioning
confidence: 99%